2021
DOI: 10.1037/cbs0000263
|View full text |Cite
|
Sign up to set email alerts
|

Selection tool use in Canadian tech companies: Assessing and explaining the research–practice gap.

Abstract: Hiring the right people at the right time is essential for the successful growth of any organization. Although organizational researchers have identified the most reliable and valid methods for selecting employees, many companies are not following these recommendations and are missing out on top talent as a result. In the present research we focus on the selection methods of tech companies using a two-study, mixed-methods design. In Study 1 we surveyed 120 tech company representatives who were knowledgeable ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…There were indications that increased experience in HR practice leads to more biased attitudes towards evidence-based personnel selection (Bezzina et al 2017). HR practitioners justified the use of certain selection procedures based on the applicant's suitability for the organization (e.g., compatibility with an organization's culture) rather than on validity concerns (Risavy et al 2021). However, other qualitative studies showed that HR professionals consider a variety of dimensions when deciding whether to conduct a selection procedure, but certain aspects seem to be of particular importance to them (e.g., generalizability-specificity of job characteristics, breadth of focus, fakability; König et al 2011).…”
Section: Findings Obtained From Qualitative and Mixed-methods Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There were indications that increased experience in HR practice leads to more biased attitudes towards evidence-based personnel selection (Bezzina et al 2017). HR practitioners justified the use of certain selection procedures based on the applicant's suitability for the organization (e.g., compatibility with an organization's culture) rather than on validity concerns (Risavy et al 2021). However, other qualitative studies showed that HR professionals consider a variety of dimensions when deciding whether to conduct a selection procedure, but certain aspects seem to be of particular importance to them (e.g., generalizability-specificity of job characteristics, breadth of focus, fakability; König et al 2011).…”
Section: Findings Obtained From Qualitative and Mixed-methods Studiesmentioning
confidence: 99%
“…This is consistent with other studies showing that HR practitioners value empirical evidence (e.g., Bailey 2022). However, the actual implementation is perceived as challenging due to difficulties in evaluating research results properly, lack of time, and limited access to journals (e.g., Risavy et al 2021). In this context, an early case study has shown that by encouraging close collaborations between HR departments and academic institutions, companies can effectively remove certain barriers and facilitate evidence-based change processes (Hamlin et al 1998).…”
Section: Findings Obtained From Qualitative and Mixed-methods Studiesmentioning
confidence: 99%
See 1 more Smart Citation